Students’ Perception and Expectation towards Pharmacy Education: A Qualitative Study of Pharmacy Students in a Developing Country - Choi, Yolanda; Wang, Jiangtao; Zhu, Yuxi; Lai, Wing-Fu (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Pharmacy education is a vital element sustaining the supply of pharmacists to meet the needs in the social and health care sectors. Understanding the perception and expectation of pharmacy students towards their study is pivotal to the maintenance of public health services in a country. Objectives: This study uses China as a sample of developing countries and seeks implications for the future development of pharmacy education. Methods: A total of 20 undergraduate students majoring in pharmacy at a university in the Guangdong province participated in in-depth individual interviews. Content analysis was adopted. Results: Four main themes were identified: intention of pursuing pharmacy education, need satisfaction by pharmacy education, implementation of pharmacy education and passion for a pharmacy practice. Conclusion: The poor motivation of pharmacy students and the low social status of pharmacists are some of the factors that may need to be addressed so as to enhance pharmacy education in developing countries in which the orientation of pharmacy education as well as the social status of pharmacists are similar to that in China.
Keywords: Pharmacy; Education; Student engagement; Expectation; Motivation